Ways of Tourism Development in Uzbekistan - Turaev Bakhodir Hatamovich; Saidov Abdullo Shukhratovich (Indonesian Journal of Law and Economics Review, 2020)
Over the past decades, tourism has become an important sector of the economy. The importance of tourism is important not only for the economy, but also for human development in the social and cultural aspects. The active tourism sector is considered to be youth. According to the World Tourism Organization, the number of tourists among young people is growing among tourists around the world. The UNWTO predicts that by 2020 there will be nearly 370 million international youth trips per year. The tourism industry in Uzbekistan has significant development potential. Uzbekistan has a very large tourism and recreational potential. On the territory of the country there are more than 7400 monuments of architecture and art of different eras and civilizations, many of which are included in the UNESCO World Heritage List. This article describes the measures taken to develop the tourism industry in Uzbekistan over the past 3 years, as well as gives tips on the development of youth tourism in Uzbekistan.